Evaluating alternative policy responses to higher world food prices: The case of increasing rice prices in Madagascar - Coady, David; Dorosh, Paul A.; Minten, Bart (International Food Policy Research Institute, 2008)
Higher world food prices have led many governments in developing countries to adopt policy measures to mitigate the adverse impact on low-income households. This paper sets out a partial equilibrium framework to evaluate the relative efficiency, distributional, and revenue implications of alternative policy responses. The model is applied to Madagascar data to evaluate the net welfare impact of reductions in rice tariffs and to compare this to the alternative policy of targeted transfers. Lowering tariffs is not a cost-effective approach to protecting low-income households due to substantial leakage of benefits to higher income households and an adverse impact on poor net rice producers even when the substantial efficiency gains from such tariff reductions are incorporated into the analysis. Developing a system of well-designed and -implemented targeted direct transfers to poor households is thus likely to be a substantially more cost-effective approach to poverty alleviation, especially if these can be linked to productivity-enhancing investments. Such an approach should be financed by switching revenue raising from rice tariffs to more efficient tax instruments. These policy conclusions are likely to be robust to the incorporation of general equilibrium considerations.